2023
DOI: 10.1097/js9.0000000000000305
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic versus open repeat hepatectomy for recurrent hepatocellular carcinoma: a systematic review and meta-analysis of propensity score-matched cohort studies

Abstract: Objective: The effectiveness of laparoscopic repeat hepatectomy (LRH) versus open repeat hepatectomy (ORH) on recurrent hepatocellular carcinoma (RHCC) is unclear. We compared the surgical and oncological outcomes of LRH and ORH in patients with RHCC with a meta-analysis of studies based on propensity score-matched cohorts. Methods: A literature search was conducted on PubMed, Embase, and Cochrane Library with Medical Subject Headings terms and keywords… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Surgical resection is the only curative option, with sorafenib as the sole approved drug for HCC [ 3 ]. The 5-year survival rate for liver cancer remains under 30% [ 4 ]. Recent research underscores the critical role of RNA epigenetic dysregulation in liver cancer progression, with N6-methyladenosine (m6A) modifications being a key factor.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical resection is the only curative option, with sorafenib as the sole approved drug for HCC [ 3 ]. The 5-year survival rate for liver cancer remains under 30% [ 4 ]. Recent research underscores the critical role of RNA epigenetic dysregulation in liver cancer progression, with N6-methyladenosine (m6A) modifications being a key factor.…”
Section: Introductionmentioning
confidence: 99%
“…We read with great interest the recent meta-analysis by Xiang et al 3 , reporting the surgical and oncological outcomes of LRH and open repeat hepatectomy (ORH) for RHCC. The authors included five studies involving a total of 818 patients and concluded that LRH might be a preferable treatment option for RHCC.…”
mentioning
confidence: 99%